1980
DOI: 10.1002/jez.1402140203
|View full text |Cite
|
Sign up to set email alerts
|

Variability of response of early Drosophila embryos to heat shock

Abstract: Several embryonic stages (nuclear multiplication stage up to blastoderm) were incubated at 37°C. The 84,000 dalton heat-shock protein was always present in the heat-shocked embryos at all these stages. This protein was also found in nonheat-shocked controls. Different amounts of two other heat-shock proteins, the 70,000 and 68,000 daltons, were synthesized depending upon the embryonic stage. A massive synthesis of these two later proteins was observed in embryos which were able to recover from the heat-shock.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 16 publications
6
42
0
Order By: Relevance
“…A similar observation has been reported for very early embryos of Drosophila melanogaster (10,24 (8,10,23). In this report, as Wittig et al (31) have previously reported, we showed that the same result is true for the eight-cell mouse embryo.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A similar observation has been reported for very early embryos of Drosophila melanogaster (10,24 (8,10,23). In this report, as Wittig et al (31) have previously reported, we showed that the same result is true for the eight-cell mouse embryo.…”
Section: Discussionsupporting
confidence: 92%
“…They transiently synthesize high levels of the same set of very conserved polypeptides, the heat shock proteins (HSP). A developmental control of the synthesis of these proteins has been previously demonstrated (8,10,23,24,26) In preblastoderm Drosophila embryos (8,10,24), high levels of some HSP are spontaneously expressed in the absence of stress, whereas the other HSP could not be induced by heat treatment.We have previously shown (2) (20,22,27 Hyperthermia. Cells were grown in tissue culture dishes (diameter, 35 mm).…”
mentioning
confidence: 95%
“…These authors referred to it as 'the comet'. In early Drosophila embryos (Graziosi et al, 1980;Loyd et al, 1981) the HSP equivalent to the mouse 89-kd and 70-kd have also been found to be spontaneously very abundant. In addition, the heat induction of HSP synthesis is reported to depend heavily upon the embryonic stage in Gel electrophoresis Isoelectrofocusing (O'Farrell, 1975) was performed with 15 cm polyacrylamide gels containing 1.6%7 3.5/10 and 0.4% 4/6 ampholines (LKB): 550 V were applied to the gel tubes for 16 h and then 1000 V for 1 h. Gels were extruded and kept at -20°C until used for the second dimension.…”
Section: Ec Cellsmentioning
confidence: 99%
“…Fifth, the 63B region is induced to puff in isolated salivary gland nuclei in response to uninduced cellular extracts that do not cause puffing at other heat shock loci (8). Sixth, hsp83 is a common protein in early embryos kept at normal growth temperatures, and is also the only heat shock protein detectable in heat-induced unfertilized eggs (9). Furthermore, of the seven major heat shock genes only the mRNAs encoding hsp83, hsp27, and hsp26 are present during normal development in non-heat shocked adult ovaries and in preblastoderm embryos.…”
Section: Introductionmentioning
confidence: 99%